PERAN SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN SIDOARJO DALAM MENGENDALIKAN DINAMIKA POLITIK DI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN SIDOARJO - Ismail; Tri Prasetijowati; Riska Hidayati (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
Political dynamics is an illustration of how far the political process is taking place so that it is able to reflect the values of democracy and accountability. With this political dynamics, there will be political movements that emerge because of the internal and external demands of the party as an organized group which is the impact of community interaction. So that it will bring up new regulations as a result of these political movements. This study aims to analyze the role of the DPRD Secretariat in controlling political dynamics in the Sidoarjo Regency DPRD. Then to analyze the factors that influence the DPRD Secretariat in controlling political dynamics in the Sidoarjo Regency DPRD, as well as to analyze the efforts of the DPRD Secretariat in controlling political dynamics in the Sidoarjo Regency DPRD. This study uses qualitative research methods, with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the role of the Sidoarjo Regency DPRD Secretariat in controlling political dynamics in the Sidoarjo Regency DPRD is to provide support for the implementation of the duties and functions of the Sidoarjo Regency DPRD and facilitate all the needs and needs of DPRD members in carrying out their functions, one of which is in the legislative field. As for carrying out its role, the Sidoarjo Regency DPRD Secretariat also has factors that influence its role which consist of inhibiting factors and supporting factors. As well as the efforts made by the Sidoarjo Regency DPRD Secretariat in controlling political dynamics in the Sidoarjo Regency DPRD consisting of 2 ways, namely by optimizing the budget for facilities and infrastructure and increasing employee productivity and capabilities. So that with these efforts can control the political dynamics in the Sidoarjo Regency DPRD.